Measuring the effectiveness of work–life balance strategies in the manufacturing sector - Idris O. Ganiyu; Evelyn Derera; Sulaiman O. Atiku; Ziska Fields (SA Journal of Human Resource Management, 2020)
Orientation: The development of an appropriate framework to measure the effectiveness of work–life balance strategies (WLBS) among manufacturing firms in Nigeria is still a major challenge. Research purpose: The main purpose of this article is to measure the effectiveness of WLBS in the manufacturing sector, drawing insights gathered from two selected manufacturing firms in Lagos metropolis, Nigeria. Motivation for the study: Despite the global explosion of research on work–life balance, there is a dearth of studies measuring the effectiveness of WLBS adopted by manufacturing firms in Nigeria. Research approach/design and method: A structured questionnaire was adopted to gather data among 312 employees of the two selected manufacturing firms in Lagos Metropolis, Nigeria. Structural Equation Modelling was valuable in establishing the mediating influences of WLBS and work-family satisfaction on the interplay between work-family stressors and the selected manufacturing firms’ performance. Main findings: The study findings revealed that WLBS and work–family satisfaction mediate the interplay between work–family stressors and the selected manufacturing firms’ performance. Practical/managerial implications: To enhance continuous performance, human resource managers of the manufacturing firms should ensure the improved implementation and adoption of relevant WLBS that could help the employees cushion the effect of work and family stressors thereby achieving satisfaction with work and family life. Contribution/value-add: This study develops and validates a framework to measure the effectiveness of WLBS in selected manufacturing firms, Lagos Metropolis. The developed framework could serve as a template which could be replicated in other sectors of the Nigeria’s economy.